Keunggulan Kompetitif UKM Sentra Pengolahan Kerupuk Ikan dan Udang di Indramayu Berbasis Sumber Daya - Trisna Ningsih; Sugeng Hari Wisudo; Martani Huseini; Achmad Poernomo; Tri Wiji Nurani (Institut Pertanian Bogor, 2012)
The concept of resource based focus on modifying organizational capabilities into company's competitive advantage, which is the achievements of the unique, rare, cannot be duplicated and cannot be replaced combination between company's resources and assets. The purpose of this research is to identify the resources, capabilities, and core competencies owned by the SMEs of fish and shrimp crackers in the Indramayu processing center, and their development strategies. The competitive advantage of the SMEs of fish and shrimp crackers in the Indramayu processing center was analyzed using network analysis, while its dynamic capabilities was analyzed using Soft Systems Methodology (SSM). After the core competencies were identified, the next step was formulating the strategic routing for the SMEs of fish and shrimp crackers in Indramayu processing center. The research shows the time required to produce 3.550 kgs of fish crackers with 100 labour are 2.070 minutes, so the level of efficiency was 33.5 kgs/20,7 minutes/person. Some alternative development strategies required for the SMEs of fish and shrimp crackers in the Indramayu processing center to realize the strategic routing are (1) organizational restructuring, (2) business reengineering, and (3) business revitalizing. Key words: competitive advantage; SMEs processing center; fish and shrimp crackers; resource based